2020
DOI: 10.3390/ma13122720
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Low-Frequency Electromagnetic Casting on Micro-Structure and Macro-Segregation of 5A90 Alloy Ingots

Abstract: The effect of low-frequency electromagnetic fields on the micro-structure and macro-segregation of 5A90 alloy ingots during the semi-continuous casting process were quantitatively investigated. The ingots of a 5A90 alloy with a diameter 170 mm were produced by the conventional direct chill casting (DCC) process and low-frequency electromagnetic casting (LFEC) with 10 Hz/100 A. The results showed that LFEC can substantially refine the micro-structure and shorten the width of the columnar grain area of an ingot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, the details of the grain refinement mechanisms under pulse magnetic fields remain to be elucidated [22]. Some researchers have suggested that the main reason for grain refinement under pulsed magnetic fields is the strong stirring of the melt in the crystallizer due to the Lorentz force, which leads to dendrite fragmentation, and ultimately, those fragments become the nucleus, increasing the nucleation rate [23][24][25]. However, other researchers revealed that the energy of the magnetic field can reduce the energy barrier and improve the nucleation rate [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the details of the grain refinement mechanisms under pulse magnetic fields remain to be elucidated [22]. Some researchers have suggested that the main reason for grain refinement under pulsed magnetic fields is the strong stirring of the melt in the crystallizer due to the Lorentz force, which leads to dendrite fragmentation, and ultimately, those fragments become the nucleus, increasing the nucleation rate [23][24][25]. However, other researchers revealed that the energy of the magnetic field can reduce the energy barrier and improve the nucleation rate [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the abovementioned problems can be solved by using electromagnetic stirring (EMS) during DCC [ 12 , 13 , 14 , 15 ]. However, the skin effect applies to conventional EMS, demonstrating that the penetration depth of the magnetic field into the melt is limited [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the original article [ 1 ], there was a mistake in Figure 4 as published. The scale of vertical axis is wrong.…”
mentioning
confidence: 99%
“…In the original article [1], there was a mistake in Figure 4 There was also an error in the original article. A correction has been made to Section 3.2.…”
mentioning
confidence: 99%
See 1 more Smart Citation